Advanced Modeling with the MATLAB Reservoir Simulation Toolbox (Cambridge University Press, 2022)
A follow-up to An Introduction to Reservoir Simulation using MATLAB/GNU Octave, this book introduces more advanced functionality recently added to the open-source MATLAB Reservoir Simulation Toolbox (MRST). Like the original textbook, it will be invaluable for researchers, professionals and advanced students using reservoir simulation methods.